2014
DOI: 10.1007/s00345-014-1279-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of partial nephrectomy: results from a contemporary national prospective multicenter study

Abstract: Partial nephrectomy for renal cell carcinoma is commonly used in this French centers sample. Mini-invasive approaches represent also a significant part of all partial nephrectomies with no difference in terms of complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…Studies in which cold ischemia was used in the OPN group were excluded. Pooling data from 8 studies [14,15,19,21,22,24,26,27] that assessed WITs in 1386 patients showed significantly longer WIT in the RAPN versus OPN groups (WMD [95% CI]: 3.65 [0.75, 6.56], p=0.01)…”
Section: Warm Ischemia Timementioning
confidence: 96%
See 3 more Smart Citations
“…Studies in which cold ischemia was used in the OPN group were excluded. Pooling data from 8 studies [14,15,19,21,22,24,26,27] that assessed WITs in 1386 patients showed significantly longer WIT in the RAPN versus OPN groups (WMD [95% CI]: 3.65 [0.75, 6.56], p=0.01)…”
Section: Warm Ischemia Timementioning
confidence: 96%
“…after excluding studies [14,17,21,26,28,29] with obvious selection bias. Of the excluded studies, three of them [14,21,29] …”
Section: Estimated Blood Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we observed a transfusion rate of 8.6%, which is clearly above the approximate 5% rate of transfusion, which has been published for open-partial nephrectomies in a large series. However, these studies did not specifically analyze high-risk tumors and did have a warm ischemia time of up to 17 min [4,30]. A preliminary series of robotic and laparoscopic approaches for complex tumors report estimated blood loses around 250 ml.…”
Section: Discussionmentioning
confidence: 99%